Proyecto de factibilidad para la producción y comercialización de arepas de maíz, para la ciudad de Loja - GUZMÁN ROJAS, KAREN TATIANA (2017)
The present research work denominated FEASIBILITY PROJECT FOR THE PRODUCTION AND COMMERCIALIZATION OF AREPAS DE MAÍZ FOR THE CITY OF LOJA, had as general objective to carry out a feasibility study to determine the creation of a company producing and commercializing corn arepas for the city of Loja. Scientific, descriptive, analytical, inductive and deductive methods were used, as well as bibliographic techniques, a survey applied to 396 families and 20 suppliers from the city of Loja. With the market study it was possible to determine that the potential demand is 52,827, real demand of 20,658,949; effective demand 14,254,675 and in relation to the offer was determined to be 69,533, which allowed to determine the unsatisfied demand is 14,185,142. The results obtained in the financial study were determined to need to invest in fixed assets $ 31,831.80; in deferred assets $ 5,485.20 and $ 13,569.76 in current assets is needed, giving us an investment of $ 50,886.76, plus the sale price of each corn arepa for the first year will be 0.26 plus 25% of profit margin gives us the price of $ 0.32 giving a total income of $ 196,958.36. In the statement of profit and loss in the first year, a net income of $ 23,505.01 will be obtained. At the equilibrium point, it originates in sales of $ 106,407.21 and an installed capacity of 54.03% in the first year of production. The following results were obtained in the financial evaluation. The VAN 167,761.88; the IRR 63.55%; PRC, is 1 year 7 months and 24 days; RB / C, is $ 1.25; The sensitivity analysis resulted in a 13.31% increase in costs and a 10.26% decrease in revenues. It is concluded that the project is feasible and the production and commercialization of corn arepas is recommended. At the end of the procedure, the feasibility of the investment project could be concluded; therefore, it is recommended to put execution into practice, since through the financial evaluation it was possible to determine the feasibility that would contribute significantly to the economy of the sector.